2016
DOI: 10.1039/c6ra08039a
|View full text |Cite
|
Sign up to set email alerts
|

Structure–charge transfer property relationship in self-assembled discotic liquid-crystalline donor–acceptor dyad and triad thin films

Abstract: The photophysical properties of donor-acceptor (D-A) and donor-acceptor-donor (D-A-D) liquid crystalline dyads and triads based on two different discotic mesogens are examined in thin films by steady-state optical spectroscopy and subpicosecond transient absorption measurements. In these systems, triphenylene and perylene bisimide units are covalently linked by flexible decyloxy chain(s) and act as an electron donor (D) and acceptor (A), respectively. These discotic liquid-crystalline systems form well-separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 71 publications
1
31
0
Order By: Relevance
“…Transient absorption spectroscopy. The femtosecond transient absorption measurements carried out in transmittance mode were performed according to previous works, 54 while identical dynamics were confirmed in reflectance mode. Both modes used pump and probe pulses generated by a Ti:Sapphire regenerative amplifier (Spitfire Pro XP, Spectra-Physics) working with an 800 nm output.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient absorption spectroscopy. The femtosecond transient absorption measurements carried out in transmittance mode were performed according to previous works, 54 while identical dynamics were confirmed in reflectance mode. Both modes used pump and probe pulses generated by a Ti:Sapphire regenerative amplifier (Spitfire Pro XP, Spectra-Physics) working with an 800 nm output.…”
Section: Methodsmentioning
confidence: 99%
“…Connected by a decyloxy flexible bridge, the TriPh (D) and PerDi (A) units are prone to self-assemble in a solid state multisegregated D-A columnar structure at the local range. 53,54 Grazing Incidence X-ray Scattering (GIXS) of the dyad films on Al 2 O 3 surfaces revealed a spontaneous planar orientation of columnar hexagonal structures (Col h ) consisting of domains of lying columns as illustrated in Figure 1 |b2 and SI- Figure 1|. The annealing step in the fluid state of the mesophase only develops the long-range order enhancing the regularity of structure and the planar orientation.…”
mentioning
confidence: 99%
“…Finally, the wave function should be designed in such a manner as not to neglect the instantaneous correlation between the electrons' movements in response to their mutual electrostatic repulsions." Although this is the argument advanced in that study [27], Ivanov et al [66] demonstrated that the frontier orbitals are game makers in that the extent of orbital overlap greatly assists in the rationalization of the role played by polaron localization and delocalization, a topic of significant interest in the rational design of novel charge-transfer materials [67][68][69][70].…”
Section: Introductionmentioning
confidence: 96%
“…Since the so-called p-n heterojunction exists at the molecular level, these D-A DLCs possess fast intramolecular photoinduced electron transfer and form charge separated states [29][30][31][32][33]. Some D-A DLCs yield dual pathways along molecular columns to transfer electrons and holes [34,35].…”
Section: Introductionmentioning
confidence: 99%